A multimodalidade em anúncios publicitários de beleza veiculados em mídia digital sob o enfoque crítico-discursivo - Karla Mariana Souza e Santos (2022)
Technological artifacts increasingly invade our daily lives in contemporary society, which contributes to making human forms of communication increasingly sophisticated, that is, composed of image configurations, layouts and designs. In this context, a recurring process of integration of verbal and non-verbal semiosis emerges, especially in the digital environment, which are widely produced and configured among themselves in the composition of different genres, such as advertising. Considering this perspective, it is necessary to verify the functioning of these multimodal elements that circulate frequently. Therefore, the main objective of this work is to verify how advertisements are able to build different meanings from the union of multisemiotic mechanisms and how such meanings can infer the behavior and actions of the idealized consumers, acting in their identity construction. The analysis is based on Systemic-Functional Grammar (Halliday, 1978; 1994), the Grammar of the Visual Design (Kress and van Leeuwen, 2006; 2021), and Critical Discourse Analysis (Fairclough, 1994; 1995; 2001). The research is based on an analysis that includes integrating linguistic, imagery and ideological aspects, in order to answer some questions: (a) to what extent the chosen processes and their relationship with the participants and circumstances can promote the construction of a network of ideational meanings?; (b) how do the modality system components act in an attempt to reproduce social relations?; (c) at what level are visual elements, based on representational, interactional and compositional metafunctions, able to influence consumers to purchase certain products?; (d) how do verbal and visual elements articulate and interact in the construction of discourses capable of turning advertisements into tools that generate identities, ideologies, stereotypes and transform social practices? The results show that different semiosis can be produced and organized by advertising to achieve not only the specific purposes for which they are intended, but also to promote the propagation of ideas, values and customs in vogue, with the purpose of dictating consumption habits, styles of life and even influence the identity formation of idealized consumers.